PRESUPPOSITIONS IN JOSEPHINE’S UTTERANCES IN LOUISA MAY ALCOTT’S LITTLE WOMEN - Lubis, Sazidah; Suhadi, Jumino; Ezir, Ely (JOURNAL OF LANGUAGE, 2025)
This research explores the use of presuppositions by Josephine March, the main character in Little Women, a novel written by Louisa May Alcott. The objectives of this study are to describe the types of presuppositions employed by Josephine and to interpret the implied meanings within her utterances throughout the novel. This study adopts a descriptive qualitative method and applies George Yule’s classification of presuppositions, which includes six types: existential, factive, lexical, structural, non-factive, and counterfactual. The data were collected from selected dialogues spoken by Josephine in the novel. All six types of presuppositions were identified, with the following distribution: existential (29%), factive (23%), lexical (14%), structural (17%), non-factive (8.5%), and counterfactual (8.5%). The findings indicate that existential and factive presuppositions are the most frequently used, reflecting Josephine’s dynamic environment, strong personality, emotional depth, and complex relationships with others. Her language reveals her values, inner conflicts, and character development. This study demonstrates that presuppositions play a vital role in literary character portrayal and deepen the reader’s understanding of the narrative. The implied meanings within Josephine’s utterances are interpreted through contextual analysis, as context is a crucial element in pragmatic studies. The conversational context in Little Women is analyzed based on four key factors: (1) participants, (2) setting or social context, (3) topic of conversation, and (4) function of the interaction.